Interactions between monetary policy and fiscal policy - Afonso, António (2014)
Using a panel data set of 14 EU countries from 1970 to 2012, we study the type of monetary and fiscal policies of both authorities, and assess how they are influenced by certain economic variables and events (the Maastricht Treaty, the Stability and Growth Pact, the Euro and crises). Results show that inflation has a significant impact on monetary policy, and that governments raise their primary balances when facing increases in debt. Another goal is to characterise the type of interactions established between central banks and national governments, i.e. if their policies complement one another, or whether there is a more dominant one. Still, our results point to the lack of evidence concerning central banks’ response to fiscal policy.